Metode Mimicry-Memorization (Mim-Mem Method) dalam Meningkatkan Penguasaan Mufrodat Peserta Didik di Madrasah - Syarifah Aini; Mualim Wijaya (LP2M STIT Palapa Nusantara, 2018)
This research presented “influence method of mimicrymemorization(Mim-Mem Method) toward Mastery of vacabulary in Madrasah Aliyah Darul Lughah Wal Karomah”. The purpose of this method is to make easily undesrtanding and Master of Vocabulary to student into arabic language lesson. The first step is the teacher pronounce the words then repeated by students. This research was experimental. Whereas the data collection used speaking test method with comparative analyst technique (Non-Parametric) Mann-Whitney U-test (Uji U). To prove this research is significant or not, researchers use SPSS (Statistical Package for the Social Sciences). As for the result Mimicry-Memorization method (Mim-Mem Method) has affected to Vocabulary mastery in Madrasah Aliyah darul Lughah Wal Karomah. By using that method, student will be more active and more effective in learning arabic language lesson.